Analysis of the Influence of Assessment Center and Transformational Leadership on Career Development with Social Support as Moderation - Robertus Bima Adhi Nugroho (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
Objective: The purpose of this study is to determine the influence of the Assessment Center and analyze the influence of Transformational Leadership on the career development of personnel in the DIY Police. In addition, this study also aims to analyze the role of Social Support, both as a factor influencing career development and as a moderator in the relationship between the Assessment Center and Transformational Leadership and the career development of personnel in the DIY Police.Methods: The population in this study amounted to 10,365 personnel in the Yogyakarta Police, with a sample of 151 respondents selected using the Proportional Stratified Random Sampling method  so that each strata in the population was proportionally represented. Data collection was carried out through a questionnaire designed on a Likert scale of 1 to 5, where a score of 1 indicated "strongly disagree" and a score of 5 indicated "strongly agreed". This instrument is used to measure the variables of Assessment Center, Transformational Leadership, Social Support, and Career Development. The data obtained were then analyzed using the Structural Equation Modeling (SEM) method with the help of AMOS software to test the direct and indirect influence of independent variables on career development, as well as the role of social support moderation in these relationships.Results: Research shows that only Assessment Centers have a significant effect on career development, while transformational leadership and social support have no significant influence. These findings confirm that competency-based evaluations play more role in career advancement than leadership or social support factors. In addition, social support as moderation does not strengthen the relationship of other variables with career development, so career development strategies should focus more on structured assessment and training systems.Implications: this study shows that organizations need to strengthen the Assessment Center system as a key tool in career development, by ensuring competency-based evaluations are conducted objectively and sustainably. In addition, since transformational leadership and social support have no significant effect, career development policies should be more focused on performance-based training and promotion systems rather than relying solely on leadership or the social environment.